I was here - Forman, Gayle (New York : A Penguin Random House Company, 2013)
When her best friend, Meg, commits suicide by drinking a bottle of industrial-strength cleaner alone in a motel room, Cody is understandably shocked and devastated. She and Meg shared everything$1 (Bso how did she miss the signs of Meg's depression? But when Cody travels to Meg$1 (Bs college town to pack up the belongings left behind, she discovers that there$1 (Bs a lot that Meg never told her. About her old roommates, the sort of people Cody never would have met in her dead-end small town in Washington. About Ben McAllister, the boy with a guitar and a sneer, and some secrets of his own. And about an encrypted computer file that Cody can$1 (Bt open$1 (Buntil she does, and suddenly everything Cody thought she knew about her best friend$1 (Bs death gets thrown into question.s
Keywords: WASHINGTON